2012
DOI: 10.1104/pp.112.200964
|View full text |Cite
|
Sign up to set email alerts
|

Three Members of the Arabidopsis Glycosyltransferase Family 8 Are Xylan Glucuronosyltransferases    

Abstract: Xylan is a major component of the plant cell wall and the most abundant noncellulosic component in the secondary cell walls that constitute the largest part of plant biomass. Dicot glucuronoxylan consists of a linear backbone of β(1,4)-linked xylose residues substituted with α(1,2)-linked glucuronic acid (GlcA). Although several genes have been implicated in xylan synthesis through mutant analyses, the biochemical mechanisms responsible for synthesizing xylan are largely unknown. Here, we show evidence for bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
115
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 50 publications
6
115
1
1
Order By: Relevance
“…In Arabidopsis, the GlcA substitution of xylan (GUX) is catalyzed by a group of enzymes from the GT8 family (Lee et al, 2012a;Rennie et al, 2012). Because GUX1 and GUX2 decorate distinct xylan domains in Arabidopsis secondary walls, gux1 gux2 double mutant stems have largely unbranched xylans (Mortimer et al, 2010;Bromley et al, 2013).…”
mentioning
confidence: 99%
“…In Arabidopsis, the GlcA substitution of xylan (GUX) is catalyzed by a group of enzymes from the GT8 family (Lee et al, 2012a;Rennie et al, 2012). Because GUX1 and GUX2 decorate distinct xylan domains in Arabidopsis secondary walls, gux1 gux2 double mutant stems have largely unbranched xylans (Mortimer et al, 2010;Bromley et al, 2013).…”
mentioning
confidence: 99%
“…FLAG-GALS1 was purified as described (Rennie et al, 2012) by incubating microsomes corresponding to 0.6 mg protein with 1% Triton X-100, 50 mM PIPES-KOH, pH 7.0, 400 mM Suc, 1 mM phenylmethylsulfonyl fluoride, and Complete Mini Protease Inhibitor Cocktail (1 tablet per 10 mL; Roche) for 10 min and subsequently centrifuging at 100,000g for 30 min. The supernatant was incubated with EZview Red anti-FLAG M2 affinity gel (Sigma-Aldrich) for 3 h, washed three times with 1% Triton X-100, 400 mM Suc, 50 mM PIPES-KOH, pH 7.0, and 200 mM NaCl, and then three times with 400 mM Suc and 50 mM PIPES-KOH, pH 7.0.…”
Section: Purification Of Gals1mentioning
confidence: 99%
“…Second, IPUT1 belongs to a glycosyltransferase family that transfers sugars with a retaining mechanism resulting in a-linked sugars, consistent with the a conformation of the GlcA in GIPCs. Finally, both fluorescent protein fusions and proteomic studies have shown that IPUT1 is localized to the Golgi apparatus (Dunkley et al, 2004;Parsons et al, 2012;Rennie et al, 2012), where glycosylation of sphingolipids is expected to occur (Markham et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, several of lines of evidence led us to suspect that IPUT1 is actually an IPC glucuronosyltransferase. First, IPUT1 is closely related to both the GLUCURONIC ACID SUB-STITUTION OF XYLAN (GUX) proteins, which transfer GlcA onto the cell wall polymer xylan (Mortimer et al, 2010;Oikawa et al, 2010;Rennie et al, 2012), and the Galactinol Synthase (GolS) proteins, which transfer galactose onto inositol to synthesize galactinol (Taji et al, 2002). We reasoned that IPUT1 might use the same substrate, UDP-GlcA, as the GUX proteins while using the same acceptor, inositol (in the form of inositol phosphorylceramide), as the GolS proteins (Figure 1; Supplemental Data Set 1).…”
Section: Introductionmentioning
confidence: 99%